Uma época com duas faces: Relatório de Estágio Profissionalizante realizado na equipa de futebol masculino Sub-19 do Gil Vicente Futebol Clube, época desportiva 2023/2024 - Hugo José Braga Balão (2024)
The present internship report is the culmination of five intense years, during which I sought to absorb as much knowledge as possible and explore ways to translate that knowledge into practical situations. This report arises from my activities at Gil Vicente Futebol Clube, with the male Under-19 team, during the 2023/2024 season. Being involved at the highest level of national youth soccer brought increased responsibilities and constant work, with a strong focus on formative aspects but also to achieve results. As an intern manager, I had the opportunity to take on several responsibilities, primarily in the training process, as well as game analysis and the interpretation of statistical data. In this report, in addition to providing a conceptual overview of the game of football and its associated aspects, I offer context concerning the environment in which I developed my professional practice. This includes discussing the challenges that appeared during practice and reflecting on those experiences. The reflection of this practice reveals itself as the focal point in the development of my personal and professional identity, not limiting to what is described in this report only, because behind that there is a diary, in which I engaged in conscious and self-critical reflection. Because it was a season in which the Gil Vicente FC Under-19 team presented two distinct faces, that is, two different ways of playing in terms of the idea and principles of the game, some prominence goes to the comparison between these two periods, with the help of statistical data to confirm or refute my individual perception.